Management of Occupational Stress and Mental Health through Complementary Therapies: The Impact of Complementary Therapies on Occupational Stress and Mental Health in College Teachers (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present study was carried out on 50 college teachers including 25 male and 25 female teachers. Occupational stress and mental health status of college teachers were assessed. stress and improvement of mental health. Interview schedule was developed to gather information on socio- personal variables. Occupational Stress Index developed by Srivastava and Singh (1984) was used to assess stress among college teachers. An inventory was used to assess mental health status. Mean scores were computed for different aspects of occupational stress and overall stress. Mean scores were also computed for different components of mental health and overall mental health. Intervention booklet was prepared on complementary therapies for reducing stress and promoting mental health. It was personally given to college teachers. Only ten teachers participated in the intervention programme. Results revealed that complementary therapies results in reducing occupational stress and promoting mental health of respondents.The research findings have a scope of reducing mental health problems of teachers by reducing their occupational stress through complementary therapies.